ANALISIS MISKONSEPSI SISWA PADA MATERI FISIKA DI SMA NEGERI 8 HALMAHERA TIMUR MENGGUNAKAN CERTAINTY OF RESPONSE INDEX (CRI) - Feliks Robo; Rolles Nixon Palilingan; Aswin Hermanus Mondolang (Charm Sains: Jurnal Pendidikan Fisika, 2021)
In the physics learning process, one of the things to look out for is developing a change in the student's concept that extends the concept from incomplete concepts to complete and perfect. These concepts often deviate from the correct concept. Misconception are initial concepts that are inconsistent with the scientific concepts agreed by experts. This departure from the concept is known as a misunderstanding. This study aims to determine the extent of student misunderstandings in physics material at SMA Negeri 8 East Halmahera using the Certainty Of Response Index. The subjects used in this study were 30 students from Class XII MIA at SMA Negeri 8 East Halmahera. Retrieving data in this study in the form of a multiple choice diagnostic test (reasoned multiple choice test) 50 numbers, accompanied by the CRI (Certainty of Response Index) of the students on Effort and energy 15 items, Temperature and Heat 17 items and 18 static electricity. The data were analyzed qualitatively. From the results of the data analysis, the following conclusion emerged: The degree of misconception of material temperature and heat was 47%. This was the ultimate misconception of the three materials. This proves that most of the students do not understand the material temperature and heat compared to the material from Effort and energy with a misunderstanding rate was 13%, and the static electricity where a misunderstanding occurred was 20%. Overall, the misunderstanding among students is still low at 35%.